Amphiphilic wood powders with dual superlyophobicity enabled the switchable separation of oil-in-water and water-in-oil emulsion with high flux. Issue 4 (August 2021) - Hu, Zai-Yin; Chen, Xiao-Qing; Wang, Yi-Qing; Liu, Quanyi
Abstract: Materials with dual superlyophobicity (underwater superoleophobicity and underoil superhydrophobicity) show great promise in the switchable separation of oil-in-water (O/W) and water-in-oil (W/O) emulsion, while its preparation remains a challenge due to the contradictory demand of surface chemistries. In the present investigation, the green wood powders mainly consisted of cellulose, hemicellulose and lignin were demonstrated to be a dual superlyophobic platform by regionally wetting the hydrophilic or hydrophobic regions of the wood powders without additional modifications. The underwater oil contact angle and the underoil water contact angle of wood powders are high up to 158.0° and 161.5°, respectively. Furthermore, the wood powders feature fibrous structure, as well as a large porosity of 91.05%. Combined with the superior dual superlyophobicity and the unique fibrous structure, the wood powders enable the switchable separation of O/W and O/W emulsions efficiently. The achieved separation efficiency is as high as 99.9992%, with a flux of 4280.3 L m −2 h −1 . The wood powders also showed good recycling capability. Our strategy might provide a general avenue to design dual superlyophobic materials that could be applicable for achieving switchable separation of O/W and W/O emulsions. Graphical Abstract: ga1 Highlights: The wood powders contain both hydrophilic and hydrophobic groups. Regional wetting the hydrophilic or hydrophobic regions endows the wood powders with dual superlyophobicity. Switchable separation of W/O and O/W emulsions was achieved by the wood powders without any chemical treatments.